Expression of human estrogen receptor-α and -β, progesterone receptor, and androgen receptor mRNA in normal and malignant ovarian epithelial cells - Lau, Kin-Mang (The National Academy of Sciences, 1999)
Our understanding of the roles played by sex hormones in ovarian carcinogenesis has been limited by a lack of data concerning the mode of sex hormone action in human ovarian surface epithelial (HOSE) cells, the tissue of origin of >90% of ovarian cancers. We have compared the relative abundance of estrogen receptor (ER)α, ERβ, progesterone receptor (PR), and androgen receptor (AR) mRNA in four primary cultures of HOSE cells obtained from postmenopausal women to those found in late serous adenocarcinoma primary cell cultures and established ovarian cancer cell lines. We observed coexpression of ERα and ERβ mRNA along with AR and PR transcripts in normal HOSE cells and disruption of ERα mRNA expression as well as dramatic down-regulation of PR and AR transcript expression in most ovarian cancer cells. In contrast, levels of ERβ mRNA were unaffected by the malignant state. Additionally, a novel mutation involving a 32-bp deletion in exon 1 of ERα transcripts was detected in the SKOV3 cell line. This mutation would explain why SKOV3 was reported to be ER-positive but estrogen-insensitive. Taken together, these findings suggest that estrogens, signaling via either or both ER subtypes, may play an indispensable role in regulating normal HOSE cell functions. Therefore, loss of ERα, PR, and AR mRNA expression in HOSE cells may be responsible for neoplastic transformation in this cell type. In contrast, the roles played by ERβ in normal and malignant HOSE cells remain elusive. Finally, the coexistence of mutated ERα mRNA and normal ERβ transcripts in SKOV3 argues in favor of a dependency of ERβ action on functional ERαs.